Comparison of Ultrasound-Guided Pecto-Intercostal Fascial Block and Transversus Thoracic Muscle Plane Block for Acute Poststernotomy Pain Management After Cardiac Surgery: A Prospective, Randomized, Double-Blind Pilot Study - Kaya, Cengiz; Dost, Burhan; Dokmeci, Ozgur; Yucel, Semih Murat; Karakaya, Deniz (W B Saunders Co-Elsevier Inc, 2022)
Objective: The objective of the present study was to evaluate morphine consumption and pain scores 24 hours postoperatively to compare the effects of a bilateral pectointercostal fascial block (PIFB) with those of a transversus thoracic muscle plane block (TTMPB) on acute poststemotomy pain in cardiac surgery patients who have undergone median sternotomy. Design: Prospective, randomized, double-blinded. Setting: The operating room, intensive care unit, and patient ward at a university hospital. Participants: Thirty-nine American Society of Anesthesiologists II-to-III patients aged 18- to-80 years, scheduled for elective cardiac surgery via median sternotomy. Interventions: Patients randomly were allocated to groups scheduled to receive bilateral ultrasound-guided PIFB or TTMPB. Measurements and Main Results: The primary outcome was postoperative morphine use within the first 24 hours. Secondary outcomes were the numerical pain rating scale (NRS) scores at rest and during coughing, time of first analgesic demand from the patient-controlled analgesia (PCA) device, and rescue analgesia use. The nausea/vomiting scores, time to extubation, length of stays in intensive care and the hospital, patient satisfaction scores, and complications were also recorded. The first 24-hour morphine use did not significantly differ between the PIFB and TTMPB groups (mean +/- standard deviation [95% CI], 13.89 +/- 6.80 [10.83-16.95] mg/24 h and 15.08 +/- 7.42 [11.83-18.33] mg/24 h, respectively, p = 0.608). No significant difference between the two groups in the NRS scores at rest and during coughing was observed; the groups had similar requirements for rescue analgesia in the first 24 hours (n [%], three [15.8] and seven [35], p = 0.273, respectively). The time from PCA to the first analgesia request was longer in the PIFB than in the TTMPB group (median [interquartile range], 660 [540-900] minutes, and 240 [161-525] minutes, respectively, p = 0.002). Conclusions: PIFB and TTMPB showed similar effectiveness for morphine consumption within 24 hours postoperatively and in pain scores in cardiac surgery patients. (C) 2021 Elsevier Inc. All rights reserved.
Yücel, Semih Murat/0000-0002-8077-828X; Dost, Burhan/0000-0002-4562-1172; Karakaya, Deniz/0000-0001-8122-4943;
Keywords: Postoperative Pain; Acute; Surgical Procedures; Cardiac; Median Sternotomy; Nerve Block; Ultrasonography